Metody Teorii Stateczności Ruchu - Bieniek, Maciej (Engineering Transactions, 1955)
Basic theorems and methods of the theory of stability of motion are discussed. The considerations are confined chiefly to stability as presented by Lyapunov and to the principles of this theory.The following problems are treated in the successive sections. (1) Basic notions, definitions and general characteristics of investigation methods of stability.(2) Lyapunov's theorems for steady and unsteady motion. These are treated somewhat briefly, on the basis of the fundamental work of Lyapunov (1892).(3) The stability theorems in the first opproximation, the criteria of Routh and Hurwitz and the criterion of Nyquist are discussed. Also some examples are given of stability investigations in the first approximation and by means Lyapunov's general theorems.